A review on impact of physical factors on development of post-harvest fungal diseases of fruits - Kulkarni, Anil U (Current Botany, 2012)
This review highlights on impact of Relative Humidity (R.H.) and temperature on disease severity of fungal diseases of fruits. At high temperature, low temperature and low humidity, fungal diseases are not developed in fruits.